THE DEVELOPMENT OF ICT-BASED ASSESSMENT DATABASE WITH REINFORCEMENT ON ACCOUNTING SUBJECT AT SENIOR HIGH SCHOOL - Handayati, Puji; Ritme, Anggun (European Scientific Journal, ESJ, 2014)
This study aims to develop ICT-based assessment database by using Dokeos software. The development model in the study refers to Borg and Gall method. The procedure starts from the needs analysis, database development assessment, assessment database feasibility test, first database revision, limited field test, the second revision of the database and the final product. The research results is the development of assessment with the specifications database containing personal data of students, have a variety of questions (multiple choice, true/false, and essay length), provide reinforcement and display the report in the form of scores obtained by the students, the entire student scores, average result and needed time diagrams by the students. This ICT -based assessment database with reinforcement has website address at www.belajarasik.asia. The database has a valid assessment of 91.67 % from the material validator, in terms of ICT is valid for 91 % and according to the limited field test is valid for 87.48 %. The suggestions for further research is that the assessment database for the existing hosting capacity should be upgraded in order to accommodate more materials, protect on other websites when students are accessing the website for this ICTbased assessment database with reinforcement (www.belajarasik.asia), and if this database is used simultaneously, then each laptop and connection used have the same specifications.